Logo recognition using the line segment Hausdorff distance - Chen, Jingying. (2008)
In order to develop a logo recognition method that is robust to be employed under adverse conditions such as different scale/orientation, broken curves, added noise and occulsion, a logo recognition system based on line pattern features is proposed in this thesis.